Health and wellbeing of survivors of sexual violence and abuse attending sexual assault referral centres in England: the MESARCH mixed-methods evaluation - Lorna J O'Doherty; Grace Carter; Emma Sleath; Katherine Brown; Sarah Brown; Eleanor Lutman-White; Louise Jackson; Jon Heron; Priya Tek Kalsi; Olufunmilola C Ladeinde; Dianne Whitfield; Rachel Caswell; et al. (NIHR Journals Library, 2024)
Background One million people in England and Wales experience sexual violence and abuse each year, with nearly half experiencing serious sexual offences; around 30,000 survivors access sexual assault referral centres. Objectives This research was commissioned by National Institute for Health and Care Research to evaluate access, interventions and care pathways for survivors, especially those provided through sexual assault referral centres. Design, setting, participants The sexual assault referral centres care pathway was investigated through six sub-studies. There were two Cochrane Reviews (4274 participants). Seventy-two providers and 5 survivors were interviewed at eight sites; the children and young people study involved 12 participants from two sexual assault referral centres. A cohort study involving three-wave data collection over 1 year (21 sites; 2602 service users screened, 337 recruited) used a multilevel modelling framework to explore risk factors for burden of post-traumatic stress disorder symptoms at baseline and change at 1 year. We analysed costs and outcomes and conducted a narrative analysis (41 survivors). We worked closely with survivors and prioritised the safety/welfare of participants and researchers. Results Cochrane Reviews identified large effects from psychosocial interventions for post-traumatic stress disorder and depression. Sexual assault referral centres delivered a high-quality frontline service for survivors but groups experiencing domestic abuse and some ethnic and cultural minorities were under-represented. The qualitative research emphasised inter-agency collaboration for survivor benefit. The cohort study identified a risk 'triad' of adverse childhood experiences, poor mental health and economic deprivation, which was associated with baseline trauma burden. There were important improvements in trauma symptoms a year later. These improvements were unrelated to different sexual assault referral centre models. Costs and other outcomes were also similar across models. Harmful policing and justice practices/procedures were identified by 25% of participants. In this context, trauma-competent interviewing techniques, regular/timely updates and conveying case decisions with care signalled good practice. Limitations The cohort study lacked a comparison group, reducing confidence in the finding that access to sexual assault referral centres explained the reduction observed in post-traumatic stress disorder. Conclusions and future work Barriers to access call for concerted efforts to implement trauma-informed universal health services. The risk 'triad' underscores the value of holistic approaches to care at sexual assault referral centres and timely follow-on care. Poor mental health was the main barrier to service access beyond sexual assault referral centres. The persistence of trauma symptoms a year after accessing sexual assault referral centres signals urgent need for tackling counselling wait-lists, expanding support options and commitment to lifelong care. Multidisciplinary evaluation of sexual assault referral centres for better health provides a foundation for advancing trauma-informed practices in the context of sexual violence and abuse. Study registration This study is registered as ISRCTN30846825 https://doi.org/10.1186/ISRCTN30846825 Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 16/117/04) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 35. See the NIHR Funding and Awards website for further award information. Plain language summary What was the question? Around 30,000 survivors of rape, sexual assault and sexual abuse access sexual assault referral centres in England each year. Sexual assault referral centres provide support, health care and, if people wish, can gather evidence for a criminal investigation. Sexual assault referral centres also open routes to other care/support. We intended to understand the benefits of sexual assault referral centres and ways to improve care. What did we do? We interviewed 72 professionals to understand how they worked together. We followed up 335 survivors over 1 year after visiting a sexual assault referral centre. We gathered the views of 12 children and young people and 41 people from minority and disadvantaged backgrounds. We examined existing research to gather evidence of the benefit of care/support. We worked with survivors to confirm the safety and relevance of our research. What did we find? Participants were positive about sexual assault referral centres and Independent Sexual Violence Advisors, reporting very low harms (1% viewed sexual assault referral centre services as harmful to them). They were also satisfied with charities offering counselling, helplines and advocacy (4% harms). The research gathered mixed feedback about the National Health Service and police, with more harm being reported (15% and 25%, respectively). We found gaps in NHS care for those with complex trauma and long-term mental health problems. Post-traumatic stress disorder affected 70% of participants, with the highest being observed for those with adverse childhood experiences, poor mental health and economic struggles (a risk 'triad'). Improvements occurred 1 year later, although half of participants still had trauma symptoms. We identified new treatments (e.g. yoga) as potential alternatives to traditional interventions. What does this mean? Sexual assault referral centres offer excellent care to survivors but should be accessible to a wider group of people. Identifying, supporting and careful referral of those with the risk triad mentioned may aid recovery after sexual violence and abuse. The research suggests that the NHS and policing/justice needs to ensure that they provide good care more often. Scientific summary Background Approximately 30,000 victims and survivors of rape, sexual assault and sexual abuse access sexual assault referral centres (SARCs) each year; therefore, there has been an urgent need to assess the experiences of these services. There is also a need to improve options for care; the visibility of and access to SARCs; and collaboration within frontline specialist services to serve people of all ages and genders exposed to sexual assault and rape in England. This research was commissioned by the National Institute for Health and Care Research (NIHR) to evaluate the provision of SARCs. We intended to determine the extent to which SARCs meet the needs of victims and survivors of recent and non-recent sexual violence and abuse, including children, young people and other survivors who may be silenced across different communities in Britain. Objectives The multidisciplinary evaluation of sexual assault referral centres for better health (MESARCH) project addressed a range of research questions, allowing for the evaluation of SARCs and expanding evidence for different services and interventions across SARC care pathways.